In-plane permeability prediction model for non-crimp and 3D orthogonal fabrics. Issue 8 (3rd August 2018) - Karaki, M.; Hallal, A.; Younes, R.; Trochu, F.; Lafon, P.
Abstract: Permeability reflects the ease of flow inside a composite fabric. A predictive model has been developed to estimate the unidirectional permeability in both, the warp and weft directions, for a family of non-crimped and 3D orthogonal fabrics. The model is based on an analytical solution derived from previous studies, in which the microscopic permeability of unidirectional fiber bundles is estimated. The implementation of this model requires basic geometrical parameters of the fabric architecture. Those parameters include the dimension of the mesopores and architecture of the fiber bundles, which are determined from pictures taken for the fabric and from the textile data sheet. In addition, the average volume of mesopores and fiber bundles are calculated for different fiber volume fractions in the warp and weft directions. The model evaluates two contributions; the first one deals with the flow inside and in between the tows, while the second one figures out the flow deviations arising from the stitching yarns. The model uses effective radius and fiber volume fraction to evaluate permeability for the two flow contributions mentioned above. An experimental investigation validates the predictive model for five different fabrics and three different fiber volume fractions. Good agreement is found.